A novel association of an uncommon pigmentation pattern: coexistence of cutis tricolor with intracranial teratoma and holoprosencephaly - (:unkn) unknown (My University, 2014)
Cutis tricolor was first described in a 17-year-old male patient by Happle et al. as a rare coexistence of circumscribed hyperpigmentation and hypopigmentation close to each other on a background of normally pigmented skin. Cutis tricolor has been reported as an isolated cutaneous finding or in various associations. To the best of our knowledge, cutis tricolor in association with teratoma and holoprosencephaly has not been reported in the literature. Herein, we report a male patient who presented with a teratoma and a combination of whorl-like hypopigmentation together with hyperpigmented patches adjacent to each other on intermediately pigmented skin. This case report supports the view that cutis tricolor may be a marker of an underlying neurological abnormality.
Keywords: Humans; Male; Hyperpigmentation; Child; Brain Neoplasms; Seizures; Holoprosencephaly; Teratoma; Hypopigmentation; Language Development Disorders; Psychomotor Disorders